Cardiotoxicity of anticancer drugs and radiotherapy in patients with hematologic malignancies and solid tumors - L. M. Kogoniya; M. O. Rusanov; V. E. Shikina (Онкогематология, 2022)
Cardioncology has emerged as a new field at the intersection of cardiology and oncology. Despite the fact that improving efficiency of antitumor treatment increased the survival of oncological hematological patients, the long-term cardiovascular consequences of this treatment have become more clinically significant.Despite the effectiveness of modern methods of treatment, some drugs, such as Bcr-Abl kinase inhibitors, anthracyclines, HER2/Erbb2 inhibitors, vascular endothelial growth factor inhibitors, fluoropyrimidines, as well as radiation therapy can have a pronounced effect on the cardiovascular system. These toxic effects lead to cardiac arrhythmia, heart failure, vascular toxicity and even death. It is important for hematologists, oncologists and cardiologists to understand the basic diagnostic and treatment strategies that should be used in the event of toxicity of this kind. At a time when, due to the developed cardiotoxicity, antitumor therapy should be discontinued, in some cases, it is possible to consider continuing treatment with caution and careful monitoring.